Experimenting a metric suite for backtracking design - Shaw, Wen Yeak. (2011)
Error handling is an essential feature and one of the most complex portion of a software system. However, this area has not been attended to by many. In this article, a set of metrics for determining how well a software system handles error corrections, by means of fields recoverability, fields correctability and function backtrackability is proposed. Experimentation of the metric suites is carried out for two industrial applications using empirical analysis. The experiment also shown that error handling features can be measured at an early stage of software development, using documents such as Requirement Analysis Document and Design Document. Or at a later stage while the system is running live, by studying the manual and live system runs. The evaluation result indicates that software system backtrackability can be measured. And the measurement may be used to help determine if the requirements for error handling features are well catered for in the early stage of system development.